Moderating effect of Ulul Albab on competitive intelligence for competitive advantage of Halal based organisation - Fatah Yasin, Raudlotul Firdaus; Basri, Badrul Shahri; Mhd. Sarif, Suhaimi (2019)
In recent times, Halal based organisation is growing at a rapid pace worldwide. Halal based organisations globally are facing many challenges in preserving their Islamic identity in accordance with the divine revelation due to the globalisation and secularism has been arisen unconsciously in various aspect of life. Lack of spiritual and ethical awareness, especially in the management of the organisations and institutions has brought them away from Islamic principle. Thus, this study provides an insight about the importance and influences Of Ulul Albab’s concept On Competitive Intelligence (CI) for the competitive advantage of halal based organisation based on Quranic approach that has not been implemented in management but widely accepted in Islamic education. This study also aimed at constructing the successful of implantation of CI and identify its moderation effect of ulul albab for competitive advantage in a halal based organisation. Thus, this study is based on the qualitative methodology by analysing data collection from both primary and secondary sources. As a result, the study shows that the ulul albab’s concept related to the enhancement of organisational’s self-development based on tawhidic paradigm which can elevate the competitive advantage of Halal based Organisation to a higher level.